Answer:
4
Step-by-step explanation:
Hope this helps. Please give brainliest.
Answer:
- As x approaches negative infinity, f(x) approaches negative infinity
Step-by-step explanation:
<u>Given function</u>
- f(x)= x^3 + 2x^2 - 5x - 6
<u>Finding zero's</u>
- x^3 + 2x^2 - 5x - 6 = 0
- x^3 - 2x^2 + 4x^2 - 8x +3x - 6 =
- (x - 2)(x^2 + 4x + 3) =
- (x - 2)(x^2 + x + 3x + 3) =
- (x - 2)(x(x + 1) + 3(x + 3)) =
- (x - 2)(x + 1)(x + 3)
<u>Zero's are</u>
<em>See the graph attached</em>
<u>Correct end behavior as per graph:</u>
- As x approaches negative infinity, f(x) approaches negative infinity
Answer:
8 people
Step-by-step explanation:
i don't know if this is correct but you have to divide 16 from 24. sorry if this is wrong im trying to do the best i can.
24 is the simplified answer